Cell Factory Design and Culture Process Optimization for Dehydroshikimate Biosynthesis in Escherichia coli - Choi, Si-Sun; Seo, Seung-Yeul; Park, Sun-Ok; Lee, Han-Na; Song, Ji-soo; Kim, Ji-yeon; Park, Ji-Hoon; Kim, Sangyong; Lee, Sang Joung; Chun, Gie-Taek; Kim, Eung-Soo (Frontiers in Bioengineering and Biotechnology, 2019)
3-Dehydroshikimate (DHS) is a useful starting metabolite for the biosynthesis of muconic acid (MA) and shikimic acid (SA), which are precursors of various valuable polymers and drugs. Although DHS biosynthesis has been previously reported in several bacteria, the engineered strains were far from satisfactory, due to their low DHS titers. Here, we created an engineered Escherichia coli cell factory to produce a high titer of DHS as well as an efficient conversion system from DHS to MA. First, the genes showing negative effects on DHS accumulation in E. coli, such as tyrR (tyrosine dependent transcriptional regulator), ptsG (glucose specific sugar: phosphoenolpyruvate phosphotransferase), and pykA (pyruvate kinase 2), were disrupted. In addition, the genes involved in DHS biosynthesis, such as aroB (DHQ synthase), aroD (DHQ dehydratase), ppsA (phosphoenolpyruvate synthase), galP (D-galactose transporter), aroG (DAHP synthase), and aroF (DAHP synthase), were overexpressed to increase the glucose uptake and flux of intermediates. The redesigned DHS-overproducing E. coli strain grown in an optimized medium produced approximately 117 g/L DHS in 7-L fed-batch fermentation, which is the highest level of DHS production demonstrated in E. coli. To accomplish the DHS-to-MA conversion, which is originally absent in E. coli, a codon-optimized heterologous gene cassette containing asbF, aroY, and catA was expressed as a single operon under a strong promoter in a DHS-overproducing E. coli strain. This redesigned E. coli grown in an optimized medium produced about 64.5 g/L MA in 7-L fed-batch fermentation, suggesting that the rational cell factory design of DHS and MA biosynthesis could be a viable way to complement petrochemical-based chemical processes.